New spectrophotometric method for the determination of gabapentin in bulk and dosage forms using p-dimethylaminobenzaldehyde. Issue 6 (2nd November 2018) - Adegoke, Olajire A.; Adegbolagun, Olayemi M.; Aiyenale, Elizabeth O.; Thomas, Olusegun E.
ABSTRACT: A new simple, accurate and economic spectrophotometric method based on azo dye derivatization for the determination of gabapentin (GBP) was developed. Critical factors were optimized. The method was validated and assay of dosage forms was done. Spot tests and TLC confirmed the formation of azo adduct. A 0.3 M NaNO2 solution using 2 M HCl was used for diazotization. The optimal temperature and time were 30°C and 10 min. Azo adducts were determined at 430 nm. Methanol was found to be the best solvent. Gabapentin coupled at a ratio of 1:1 with DMAB. The assays of GBP were linear over the range 1–6 µg/mL ( r  = 0.9973) and LOD of 0.8322 µg/mL. The methods were accurate (error < 2%) and precise (RSD < 0.5%). The methods were successfully applied to the assay of GBP in dosage forms and compared favorably with reference method ( p  > .05). The successful diazotization of gabapentin and the azo adduct formation with DMAB is reported for the first time.